Zur Anatomie von Formica pratensis Retzius, 1783. Das Gelenk zwischen Thorax und Gaster einschließlich der im Gelenkgebiet vorhandenen und der Gelenkfunktion dienenden Organe (Hymenoptera: Formicidae). - Kürschner, Isa (Contributions to Entomology = Beiträge zur Entomologie, 1970)
The present paper describes the thorax-gaster-joint of Formica pratensis Retzius, 1783. It is shown to be a double joint formed by a small stalk between thorax and gaster. The two joints are called the joint in the thorax region and the joint in the gaster region. The joint in the thorax region is a socket-joint with additional functions of a hinge joint. The levels of movement of the two joints together produce the high movability of the gaster. Among the organs of the epinotum those serving the function of the joint take up most of the space. The stomata above the joints of the third coxae proved to be the outlets of a paired gland (Odoriferous gland?). A "phon organ" at the end of the epinotum does not exist in Formica pratensis Retzius. The findings of histological cuts confirm and improve the results gained by preparation.